Pipeline on microarray data analysis: Pre-processing - Fajriyah, Rohmatul; Kongchouy, Noodchanath; Ayudhaya, Wanvisa Saisanan Na; Yotenka, Rahmadi; Danarwindu, Ghiffari Ahnaf (Universitas Ahmad Dahlan, 2025)
Bioinformatics is blooming and its data are store in some repository offline and or online. Yet some basic concepts are not fully disseminated. The paper intends to provide the reader with a review of one important concept in the pipeline bioinformatics data analysis of microarray, pre-processing. In pre-processing, there are four steps, background correction, normalization, probe correction and summarization. Each step consists of several methods, and we describe each method to give a better understanding on how it works theoretically. We focused on microarray data from Affymetrix platform with single-color chip.